Determining Basic Geometric Parameters of the Apron Conveyor Drive - Moldabayev, Baurzhan G.; Rozhkov, Alexander V.; Balabayev, Oyum T. (Communications - Scientific Letters of the University of Zilina, 2023)
The article provides an analysis of the classical design of the apron conveyor, which revealed the significant disadvantages. The study is devoted to the improvement of the plate conveyor design, which would provide an increase in the speed and performance of the conveyor, and allow to create conveyors of any required length and installation angle.
Keywords: apron conveyor; linear asynchronous motor; relative pole pitch; active element; geometric parameters; conveyor speed; angle of setting; specific traction force